Evaluacion agroeconomica de densidades de poblacion de yuca en el arreglo Mxn//y en el Distrito de Lorica - Hessen S., F. (International Center for Tropical Agriculture, 1990)
A multisite trial (6 sites) was carried out to determine the optimum plant populations for one of the most important cropping systems used in the Lorica district (Cordoba, Colombia): maize associated with yam and intercropped with cassava. Plant populations of 1.2 x 1.0, 1.2 x 1.3, and 1.2 x 1.6 m were used, varying only the plant population of cassava. Maize was planted 1st (4 grains/site) at the beginning of the rainy season, yam 20 days later (1 piece/site), and cassava 20 days after yam planting. No significant statistical differences were found in maize or yam yields among the treatments, indicating that they are not affected by cassava plant population. Fresh root yield of cassava at the 1.2 x 1.0 m plant population density, however, was statistically different from those of the other treatments (8.7, 5.6, and 5.3 t/ha, resp.). No statistical differences occurred among sites. Therefore the 1.2 x 1.0 plant density is recommended for this cropping system. (CIAT)